Voting for burden sharing rules in public goods games - Carlo Gallier; Martin Kesternich; Bodo Sturm (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2014)
In this experiment, we endogenize the choice of which contribution scheme is implemented in a public goods game. We investigate three rule-based contribution schemes. In a first step, players agree on a common group provision level using the principle of the smallest common denominator. Subsequently, this group investment is allocated according to a specific rule to individual minimum contributions. The game is implemented either as a Single- or a Multi-Phase Game. In the Single-Phase Game, the contribution schemes are exogenously implemented. In the Multi-Phase Game, we let subjects vote on the rule-based contribution schemes. If a scheme obtains a sufficient majority it is implemented. In case no sufficient majority is reached, subjects have to make their contributions to the public good using the voluntary contribution mechanism (VCM). Our results suggest that the endogenous choice of a contribution scheme has an impact on the level of contributions. In case of a rule-based contribution scheme which equalizes payoffs, contributions are higher if subjects choose the scheme than in case the scheme is implemented exogenously. In contrast, contributions are higher if the VCM is implemented exogenously than in case a sufficient majority cannot be obtained and, therefore, subjects have to play the VCM.
urn:nbn:de:bsz:180-madoc-370697
Keywords: C72; C92; H41; 330; public goods; endogenous institutions; minimum contribution rules; cooperation